A trace analysis of Korean UDCs - Lee, Sun-Hee (Proceedings of the 12th International Conference on Head-Driven Phrase Structure Grammar, 2005)
In this paper, we claim that the filler-gap linkage in Korean UDCsneeds to be handled at the level of syntax and that unboundeddependencies represented by traces, resumptive pronouns, andresumptive reflexives in Korean can be simply captured – withoutposing any extra mechanisms &